A study of Addictive Inpatients at Ibn-Rushd Psychiatric Teaching Hospital in Baghdad - Hussain, amir; Al-Aboudi, shalan (Iraqi National Journal of Nursing Specialties, 2007)
Objective :. 1-Find out the prevalence of alcohol and drugs addiction in two different years before and after the last war i.e. in 2002 and in 200. 2-Study the association between the addiction and some variables. 3-Identify the prescribed drugs and other substances that have been abused Methodology : A retrospective study has been conducted involving the in-patients at addiction unit-IbnRushd psychiatric hospital in Baghdad by applying the semi-structured form based on ICD-10 criteria of addiction and dependency with the confirmation of the specialist psychiatrist diagnosis of dependency. Data concerning each patient admitted in the hospital was gathered to have an idea about the problem of addiction (drugs and alcohol) during the year 2002 and the year 2004. The total number of the patients was 286. Results : The results showed that drug addiction was significantly increased more than alcohol, 73% of admissions in 2002 were alcoholic while in 2004, 40.8% of in-patients were alcoholic. In 2004, the drug addiction in patients was 58.2% and in 2002 was only 27%, which was statistically significance. All patients were males; young age, single, and unemployed. The most common drug was benzhexol (artane) either alone or with other drugs or mixed with alcohol. Recommendation